CORELATIONS BETWEEN THE CLINICAL AND MORFOLOGICAL ASPECTS AND THE MOLECULAR MARKERS IN THE MALIGNANT TRANSFORMATION OF THE ORAL LEUKOPLAKIAS - Doinița Olinici; Laura Gheucă-Solovăstru; Tatiana Țăranu; L. Bădescu; Laura Stoica; Emanuela Ana Botez; Carmen Elena Cotrutz (Romanian Society of Oral Rehabilitation, 2016)
The leukoplakia injuries represent the most frequent premalignant oral injuries. Their clinical and histopathological features are not always significant for the malignant transformation and, implicitly, for their diagnosis. The important progress achieved in the last three decades for the understanding of the cellular and molecular mechanisms of the leukoplakia lesions have not managed to significantly reduce the prevalence of the oral squamouscellular carcinomas. Therefore, it is necessary the identification and the characterization of the molecular markers which, together with the clinical and morphological aspects, can improve the management of these lesions.